A Fault Location Algorithm for Two-End Series-Compensated Double-Circuit Transmission Lines Using the Distributed Parameter Line Model. Issue 6 (3rd April 2017) - Kang, Ning; Gombos, Gergely; Mousavi, Mirrasoul J.; Feng, Xiaoming
Abstract: A new fault location algorithm for two-end series-compensated double-circuit transmission lines utilizing unsynchronized two-terminal current phasors and local voltage phasors is presented in this paper. The distributed parameter line model is adopted to take into account the shunt capacitance of the lines. The mutual coupling between the parallel lines in the zero-sequence network is also considered. The boundary conditions under different fault types are used to derive the fault location formulation. The developed algorithm directly uses the local voltage phasors on the line side of series compensation (SC) and metal oxide varistor (MOV). However, when potential transformers are not installed on the line side of SC and MOVs for the local terminal, these measurements can be calculated from the local terminal bus voltage and currents by estimating the voltages across the SC and MOVs. MATLAB SimPowerSystems is used to generate cases under diverse fault conditions to evaluating accuracy. The simulation results show that the proposed algorithm is qualified for practical implementation.